An experimental study on the needle valve motion characteristics of high pressure natural gas and diesel co-direct injector. (15th February 2023) - Yang, Xiyu; Dong, Quan; Wang, Xiaoyan; Zhou, Tanqing; Wei, Daijun
Abstract: To reveal the gas needle valve dynamic characteristics of the high pressure natural gas and diesel co-direct injector, an innovative non-intrusive needle valve motion characteristics measurement method is proposed. The influence of needle valve movement on injection rate is investigated, and the effect of diesel pressure fluctuation on needle lift process is revealed. The results indicated that the lifting speed of the needle increases with the increase of gas injection pressure. Under the same injection pressure, the displacement curve of the needle valve changes from triangle to trapezoid with the increase in energizing time. Due to the change of the gas flow throttle position, the injection rate does not correspond linearly with the needle displacement curve. In the process of needle upstroke, there are two different velocities in the rising process of the injection rate. Furthermore, in the diesel system, the compression wave reflected from the common rail has a significant influence on the needle dynamic characteristics and injection rate which becomes more obvious with the decrease in injection pressure. Under the action of reflected compression wave, the moment delay of needle reaching the maximum position can reach 0.6 ms, and the gas injection mass can be reduced by 16%. Highlights: An innovative non-intrusive needle valve dynamic characteristics measurement method is proposed. The relationship between gas injection rate and needle valve displacement curve is nonlinear. Diesel pressure shows great impacts on the gas injection characteristics. Delayed diesel compression wave propagation can significantly improve the velocity of the needle valve.